Associations of anaemia and iron deficiency with health-related quality of life in patients with chronic kidney disease stage G3b-5 in Japan: sub analysis of the Reach-J CKD cohort study - Reiko Okubo; Tomohiro Ohigashi; Masahide Kondo; Ryoya Tsunoda; Hirayasu Kai; Chie Saito; Junichi Hoshino; Hirokazu Okada; Ichiei Narita; Shoichi Maruyama; Takashi Wada; Kunihiro Yamagata (BMC Nephrology)
Abstract Background Iron deficiency is a major contributor to anaemia in chronic kidney diseases. The association of anaemia and iron deficiency with health-related quality of life in Japanese patients with non-dialysis chronic kidney disease has not been examined. In this study, we evaluated anaemia and iron deficiency in patients with chronic kidney disease G3b-5 and examined their associations with health-related quality of life. Methods This nationwide cohort study included 2,249 patients with advanced chronic kidney disease receiving nephrologist care from 31 representative facilities throughout Japan; they were randomly selected through stratification by region and facility size and aligned with the Chronic Kidney Disease Outcomes and Practice Patterns Study. Using baseline patient data, we assessed the association of anaemia and iron deficiency with health-related quality of life, employing the 36-item Kidney Disease Quality of Life Questionnaire. Results The mean mental and physical component summary scores for all patients were 49 and 47, respectively. Patients with haemoglobin levels < 10 g/dL had worse three kidney disease subscale, mental component summary, physical component summary, and subdomain scores than those with haemoglobin levels > 12 g/dL. Patients with absolute iron deficiency (TSAT < 20% and ferritin < 100 ng/mL) had worse three kidney disease subscale and mental component summary scores than those with functional iron deficiency (TSAT < 20% and ferritin ≥ 100 ng/mL). Conclusions Japanese patients with chronic kidney disease G3b-5 with anaemia or absolute iron deficiency had worse health-related quality of life. Our results provide clinical evidence of renal anaemia in Japan and will be useful for international comparisons.